Maintenance Treatment With Antipsychotic Drugs in Schizophrenia: A Cochrane Systematic Review and Meta-analysis. (12th May 2022) - Ceraso, Anna; Lin, Jessie Jingxia; Schneider-Thoma, Johannes; Siafis, Spyridon; Heres, Stephan; Kissling, Werner; Davis, John M; Leucht, Stefan
Abstract: Antipsychotic drugs are the mainstay of treatment of schizophrenia, and are known to reduce acute symptoms of the disorder. An original version of the current review, published in 2012, examined whether antipsychotics are effective for relapse prevention, compared to withdrawing these agents for people with schizophrenia or schizophrenia-like psychoses, based on evidence from randomized trials. The current report of the update of the review is focused on some newly investigated outcomes: rates of remission and recovery, change in social functioning and in quality of life. The updated review included 75 randomized controlled trials (RCTs) published from 1959 to 2017, involving 9145 participants. Although some potential sources of bias limited the overall quality, the efficacy of antipsychotic drugs for maintenance treatment in schizophrenia was clear and robust to a series of sensitivity analyses. Antipsychotic drugs were more effective than placebo in preventing relapse at 1 year (drug 24% versus placebo 61%, 30 RCTs, n = 4249, RR = 0.38, 95% CI = 0.32 to 0.45) and in reducing hospitalization (drug 7% versus placebo 18%, 21 RCTs, n = 3558, RR = 0.43, 95% CI = 0.32 to 0.57). Quality of life appeared to be better in drug‐treated participants (7 RCTs, n = 1573, SMD = −0.32, 95% CI = −0.57 to −0.07); the same for social functioning (15 RCTs, n = 3588, SMD = −0.43, 95% CI = −0.53 to −0.34). Although based on data from fewer studies, maintenance treatment apparently increased the possibility to achieve remission of symptoms (drug 53%, placebo 31%; 7 RCTs, 867 participants; RR = 1.73, 95% CI = 1.20 to 2.48) and to sustain it over 6 months (drug 36%, placebo 26%; 8 RCTs, 1807 participants; RR = 1.67, 95% CI = 1.28 to 2.19). There were no data on recovery. Antipsychotic drugs as a group were associated with more participants experiencing side effects such as movement disorders (e.g., at least one movement disorder: drug 14% versus placebo 8%, 29 RCTs, n = 5276, RR 1.52, 95% CI = 1.25 to 1.85) and weight gain (drug 9% versus placebo 6%, 19 RCTs, n = 4767, RR = 1.69, 95% CI = 1.21 to 2.35, NNTH = 25, 95% CI = 20 to 50). For people with schizophrenia, the evidence suggests that maintenance on antipsychotic drugs does not only prevent relapses and rehospitalizations, but that patients also benefit in terms of quality of life, functioning and sustained remission. These positive effects must be weighed against the backdrop of the adverse effects of antipsychotics.